Effects of core-stabilization and trunk balance exercises on clinical parameters in patients with non-specific chronic low back pain – a randomized pilot study - Fapojuwo, Oluseun Akinleye; Akodu, Ashiyat Kehinde; Ositelu, Adurayemi Esther (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. This study compared the efficacy of core stabilization (CSE) and trunk balance exercises (TBE) with flexibility training on pain-related disability (PRD), psychological status (PS) and fear avoidance belief (FAB) in patients with non-specific chronic low back pain (NSCLBP). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Twenty-eight (28) participants diagnosed of NSCLBP were randomly assigned into CSE, TBE, and control groups (CG). Participants in CSE (n=10); TBE (n=8) and CG groups (n=10) received core stabilization exercise, trunk balance exercise and back care advice respectively. All participants received flexibility training in addition to treatment in their respective groups. Assessment of outcomes were done at baseline, end of 4th and 8th week. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. There was significant improvement in all outcomes in the CSE, TBE and CG at 8weeks; PRD (p=0.005, p=0.008, p=0.005), PS: depression (p=0.005, p=0.008, p=0.007); anxiety (p=0.005, p=0.007) and FAB about work (p=0.005, p=0.007, p=0.005); about physical activity (p=0.005, p=0.018, p=0.006). Comparison of outcomes between CSE and TBE groups showed no significant difference (p>0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Both CSE and TBE with flexibility training are effective in improving PRD, PS and FAB of patients with NSCLBP.